Design of a load frequency control scheme for multiple generators based on economic dispatch - Phua, Chun Boon (Nanyang Technological University, 2020)
The objective of this project is to develop a framework combining Load Frequency Control (LFC) and Economic Dispatch (ED) scheme via LabVIEW software for multiple generators operating in parallel in a microgrid. The purpose of LFC is to maintain the power system operating frequency at nominal frequency. ED is the optimisation for economic power generation which results in cheaper operation cost. The scope of this project will be to analyse parameters such as the distribution of power, frequency variation, and cost savings achieved for the microgrid testbed as compared to theoretical values. This report discusses the methods used in the approach of designing LFC and ED schemes. Simulations were done upon completion of the LFC and ED schemes in LabVIEW program to validate those features. The next step in the project was to integrate the program with actual generators to verify the developed LFC and ED scheme effectiveness experimentally. Analysis of the results had shown that the developed LFC and ED schemes were able to maintain nominal system frequency and optimise for cost efficient power generation respectively. In addition to that, power generation for each generator were also considered and kept within their limits by redistributing power sharing when necessary. This project had successfully achieved its objectives.